PBPK Evaluation of Sofosbuvir Dose in Pediatrics Using Simcyp® - Rania Elkeeb; Anomeh Avartoomian; Amira S. Gouda; Ahmed M. Abdel-Megied; Ola Abdallah; Eman Atef (MDPI AG, 2023)
The aim of the study is to evaluate the effectiveness of the pediatric sofosbuvir weight-based dosing strategy in providing an equitable drug exposure compared to the marketed dose. The physiologically based pharmacokinetic (PBPK) modeling and simulation is a valuable tool in assessing drug dosing and toxicity in populations with physiological, pathological, and genetic pharmacokinetic (PK) variability. The PBPK model of the sofosbuvir compound was developed using Simcyp® V20. The model was developed and verified using the published sofosbuvir's physicochemical properties and clinical data from multiple studies on healthy adult volunteers, hepatitis C virus (HCV)-infected adults, and HCV-infected pediatrics. The AUC and Cmax fold ratio of (predicted/observed) fell within the acceptable range of 0.5-2 in all tested adults' data, confirming the successful development of the sofosbuvir Simcyp® compound model. Using this model, a weight-based dosing regimen of 6 mg/kg in pediatric patients was simulated and compared to the 150 mg and 200 mg approved dose for 3-6 and 6-12 y/o pediatric patients, respectively. No dose adjustment was recommended in patients ages 6-12 y/o. However, compared to the approved 150 mg for 3-6 y/o, the weight base dose provided an equitable drug exposure to adults. Further clinical studies are warranted to verify this finding.